Ecclesiastes and Song of Songs Teach the Text Commentary Series - Curtis, Edward M.; Strauss, Mark L.; Walton, John H., 1952-; Rosset, Rosalie de (Grand Rapids, Michigan : Baker Books, 2013)
"The Teach the Text Commentary Series gives pastors the best of biblical scholarship and presents the information needed to move seamlessly from the meaning of the text to its effective communication. By keeping the discussion in each carefully selected preaching unit to six pages of focused commentary, the volumes allow pastors to quickly grasp the most important information. Each unit of the commentary includes the big idea and key themes of the passage; sections dedicated to understanding, teaching, and illustrating the text; and full-color images. How do we find meaning in life when it seems futile and meaningless? Ecclesiastes takes readers on a journey pondering this timeless questions, and this commentary helps set the book within a biblical worldview in order to help teachers communicate and apply the profound truths of Ecclesiastes today. Song of Songs is full of evocative poetry, but centuries of interpretation have produced little concensus about how this unique book should be understood. Edward M. Curtis lays out the key thems of the book and provides carefully organized commentary for interpreting, teaching, and illustrating this book."--page 4 of cover
Includes bibliographical references (pages 170-173) and index
Keywords: Bible. -- Commentaries; Bible. -- Commentaries; Bible. -- Commentaries; Ecclesiastes Textual Commentary -- Song of Songs Textual Commentary